The Relationship between Environmental Sanitation and Stunting Incidence - Ni Putu Aryani; Baiq Ricca Afrida (Institut Kesehatan YARSI Mataram, 2025)
Stunting is still a global nutritional problem. One of the factors that influences stunting is environmental sanitation. The purpose of this study was to determine the relationship between environmental sanitation and stunting. This study is a quantitative study with a case-control approach. Data collection in this study was carried out in January-March 2025 in Lembar Selatan Village, West Lombok Regency, as many as 344 people. Respondents in this study were mothers who had toddlers. The sampling technique used total sampling. The independent variable is environmental sanitation consisting of clean water sources, household waste management, water and waste disposal facilities and the dependent variable is stunting. The data collection tool in this study used a questionnaire. Stunting measurement uses height per age. Data analysis in this study includes univariate analysis using percentages and bivariate analysis using the Chi-Square test. The results of the study found that most respondents had poor clean water sources (50.6%), good household waste management (57.3%), poor water and waste disposal facilities (51.7%). The analysis found that most respondents who were not stunted were with good clean water sources (92.4%), good household waste management (65.7%), good water and waste disposal (90.7%). The results showed that there was a relationship between clean water sources (p<0.001), household waste management (p=0.002) and water and waste disposal facillities (p<0.001) with the incidence of stunting. ABSTRAK Stunting masih menjadi masalah gizi global. Salah satu faktor yang berpengaruh pada stunting adalah sanitasi lingkungan. Tujuan penelitian ini adalah mengetahui hubungan antara sanitasi lingkungan dengan kejadian stunting. Penelitian ini adalah penelitian kuantitatif dengan pendekatan case-control. Pengambilan data pada penelitian ini dilaksanakan pada bulan Januari-Maret 2025 di Desa Lembar Selatan Kabupaten Lombok Barat sebanyak 344 orang. Responden dalam penelitian ini adalah ibu yang mempunyai balita. Teknik pengambilan sampel menggunakan total sampling. Variabel independen yaitu sanitasi lingkungan yang terdiri dari sumber air bersih, pengelolaan sampah rumah tangga dan sarana pembuangan air dan limbah serta variabel dependen yaitu stunting. Alat pengumpul data dalam penelitian ini menggunakan kuesioner. Pengukuran stunting menggunakan tinggi badan per umur. Analisis data dalam penelitian ini meliputi analisis univariat menggunakan persentase dan analisis bivariat menggunakan uji Chi-Square. Hasil penelitian mendapatkan bahwa sebagian besar responden dengan sumber air bersih yang kurang baik (50,6%), pengelolaan sampah rumah tangga yang baik (57,3%), serta saluran pembuangan air dan limbah yang kurang baik (51,7%). Analisis mendapatkan bahwa sebagian besar responden yang tidak stunting adalah dengan sumber air bersih yang baik (92,4%), pengelolaan sampah rumah tangga yang baik (65,7%) dan saluran pembuangan air dan limbah yang baik (90,7%). Hasil penelitian menunjukkan bahwa ada hubungan sumber air bersih (p<0,001), pengelolaan sampah rumah tangga (p=0,002) dan saluran pembuangan air dan limbah (p<0,001) dengan kejadian stunting.